PENGARUH PEMANFAATAN MEDIA INTERNET TERHADAP KREATIVITAS PENGOLAHAN DAN PENYAJIAN MAKANAN KONTINENTAL SISWA KELAS XI PROGRAM KEAHLIAN TATA BOGA DI SMK N 1 KALASAN YOGYAKARTA TAHUN PELAJARAN 2020/2021: PENGARUH PEMANFAATAN MEDIA INTERNET TERHADAP KREATIVITAS PENGOLAHAN DAN PENYAJIAN MAKANAN KONTINENTAL SISWA KELAS XI PROGRAM KEAHLIAN TATA BOGA DI SMK N 1 KALASAN YOGYAKARTA TAHUN PELAJARAN 2020/2021 - Kukut Hartatik (UNIVERSITAS SARJANAWIYATA TAMANSISWA, 2022)
The purposeof this study was to determine the effect of the use of internet media in the creativity of processing and serving continental food. This research includes ex-post facto research, research subjects are student of class XI culinary arts at SMK N 1 Kalasan. Methods of data collection using a questionnaire and observation. The data analysis technique used descriptive analysis techniques and hypothesis testing using the product moment correlation test which was preceded by the analysis prerequisite test. The results showed that (1) the use of internet media was mostly in the sufficient category with a relative frequency of 61%, (2) the creativity of processing and serving continental food was in the sufficient category with a relative frequency of 65%, (3) there was an effect of the use of internet media on creativity in processing and serving continental food in the culinary arts department of class XI students of SMK N 1 Kalasan with a value of rcount = 0.626 > rtable = 0.254, it can be said that there is a positive and significant influence on the use of internet media on the creativity of processing and serving continental food. The coefficient of determinant (R2) is 0.39.